New Roles for Vitamin D Superagonists: From COVID to Cancer - Easty, David J.; Farr, Christine J.; Hennessy, Bryan T. (Frontiers in Endocrinology, 2021)
Vitamin D is a potent steroid hormone that induces widespread changes in gene expression and controls key biological pathways. Here we review pathophysiology of vitamin D with particular reference to COVID-19 and pancreatic cancer. Utility as a therapeutic agent is limited by hypercalcaemic effects and results from clinical trials have been disappointing. Attempts to circumvent this problem have used vitamin D superagonists, with increased efficacy and reduced calcaemic effect. A further caveat is that vitamin D mediates multiple diverse effects. Some of these (anti-fibrosis) are likely beneficial in patients with COVID-19 and pancreatic cancer, whereas others (reduced immunity), may be beneficial in severe COVID-19 but detrimental in pancreatic cancer. Vitamin D superagonists represent an untapped resource for development of effective therapeutic agents. However, to be successful this approach will require agonists with high cell-tissue specificity.